Dari Doktrin ke Aplikasi: Implikasi Teologi sebagai Aplikasi John M. Frame dalam Konteks Pendidikan Teologi dan Pelayanan Gerejawi - Hendra Winarjo (Verbum Christi: Jurnal Teologi Reformed Injili, 2022)
Since modern times, the nature of theology has experienced as an unnecessary separation between theoretical-doctrinal discipline or practical application discipline. The purpose of this article is to propose the nature of theology as application and draw its implication in the context of theological education and ecclesiastical ministry. By using the conceptual analysis method, the author analyzes and uses the view of John M. Frame which argues that theology should not be seen only as an abstract theoretical doctrine, or only teaches how to live, but theology should be viewed as life itself. The implication of theology as application in the context of theological education and ecclesiastical ministry shows a bounding and an involvement between seminary and church. By viewing theology as application, the goal is not only limited to theorizing, but also to be the doers of God’s words because there is a close relationship between what is known and what is done, and vice versa.